Analysis of Secondary Metbaolite Content of Ethanol Extract of Biden Pilosa L. Leaves which has the Potential as an Antibacterial - Pulungan, Ahmad Shafwan S; Nasution, Aswarina; Puspitasari, Wina Dyah; Gultom, Rahmad H; Rahmi, Nisrina Afiqah; Munthe, Melia Ivana Br (JBIO: jurnal biosains (the journal of biosciences), 2024)
The potential of plants as an alternative medicine is a great gift. This potential can be explored through various preliminary tests. One of the preliminary tests is to analyze the content of secondary metabolite compounds using GC-MS. One of the plants known to have potential is Biden Pilosa L. The results of the GC-MS analysis showed that there were 9 compounds identified as having antimicrobial properties. This was discovered after analyzing the compound content and continuing with a literature review. The conclusion obtained was that there were 9 compounds in the ethanol extract of Biden Pilosa L leaves that functioned as antimicrobials.